Association Between Insulin Resistance and eNOS Activity in Type 2 Diabetic Iraqi Patients with Nephropathy - Naif, Nabaa Hassan; Nada, Shaymaa Z.; Darwish, Lamya A. (Scientific Journal of Medical Research, 2021)
Objectives: The current study aimed to evaluate the correlation between serum eNOS activity and other clinical characteristics in Iraqi DN subjects. Methods: A case control study was done on 130 subjects, including 50 with DN, 40 with Type 2 Diabetes Mellitus (T2DM) without DN and 40 of them were healthy control. Phenotypic data, including serum eNOS activity, lipid profile, Kidney function tests, blood glucose, insulin, HbA1c and HOMA-IR were investigated. Results: The current study shows there is non-significant difference in age, gender and BMI between DN, DM and HC groups (P- value >0.05 for both). A significant negative correlation was found between serum eNOS activity with creatinine, HOMA-IR among DN group, similar correlation between serum eNOS activity and Urea, HOMA-IR among DM group. Conclusion: We found non-significant difference in age, gender and BMI between DN, DM and HC group. A significant negative correlation was found between serum eNOS activity, Creatinine and HOMA-IR among T2DM with DN group.